KEARIFAN LOKAL DAN PELESTARIAN LINGKUNGAN (Studi Kasus di Kampung Naga, Kabupaten Tasikmalaya dan di Kampung Kuta, Kabupaten Ciamis) - Yus Darusman (Jurusan Pendidikan Masyarakat Fakultas Keguruan Ilmu Pendidikan Universitas Siliwangi, 2017)
Abstract: Environment preservation becomes very crucial for the continuation of human life since the disasters afflicting to them as the result of the wrong doers attude towards the nature. The more humans desire to exploit the nature for their importance, the more damage the nature will be, and the worse the effect suffered by human. The attitude of simple traditional society with its local wisdom has proven the existence of a harmonious relation between human importance and nature preservation. It is understandable that behind a simple life pattern possessed by traditional society, there are a lot of significance towards the continuance of human life. Without being aware that the relation between human and natural components (ecosystem) have been embodied. Ecofeminism has been existed in the traditional society, to organize the relation not only between human, but also between human and nature.The attitude of being friendly to environment (ecofeminism) is patterned in the form of suggestion and inhibition when humans are in touch with the nature, such as; someone has to be in a sacred state when enrolling a sacred forest (having ablution), it is not allowed to bring any sharp weapons inside,to pick or cut any kinds of tree, unallowed to hunt animals, etc. Keywords; local wisdom, environment preservation, ecofeminism, ecosystem, exploitation of natural resources.